Extended spectrum AmpC and metallo-beta-lactamases in Serratia and Citrobacter spp. in a disc approximation assay - Meher Rizvi; Nazish Fatima; Mohd. Rashid; Indu Shukla; Abida Malik; Aayesha Usman; Shireen Siddiqui (Journal of Infection in Developing Countries)
Objectives: This study aimed to develop a novel model for detection of extended spectrum beta-lactamase (ESBL), AmpC and metallo-beta-lactamase (MBL) producing Serratia and Citrobacter species using cefoperazone sulbactam as well as other inducer-substrate combinations in a disc approximation assay. In the absence of molecular tools in developing countries, we attempted to standardize simple phenotypic techniques for detection of beta-lactamases to allow effective patient care in our countries. These techniques have been scarcely used in Serratia and Citrobacter spp., which are emerging as significant pathogens in our region. Methodology: Clinical isolates of Serratia and Citrobacter were tested for ESBL production. Cefoperazone (CP)/cefoperazone sulbactam (CPS), piperacillin (PIP)/piperacillin-tazobactam (TZP) and ceftazidime (CAZ)/ceftazidime-clavulanic acid (CAZ-CLAV) combinations were compared for their ability to detect ESBL producers phenotypically. Multi-drug resistant strains were further tested for detection of inducible/derepressed AmpC mutants by a disc approximation assay. Isolates were screened for MBL production by Imipenem (IMI). MBL production was confirmed using Ethylenediaminetetraacetic acid (EDTA) in a double disc synergy assay and Hodge test. Minimal inhibitory concentration (MIC) was performed for CP, CPS and IMI by agar dilution method for all isolates of Serratia and Citrobacter spp. Results: Thirty-three percent of isolates of Serratia spp. and 35.4% of Citrobacter spp. were ESBL producers. CPS was a more sensitive inducer of ESBL than TZP and CAZ/CAZ-CLAV. AmpC producers were detected in 25.6% of the isolates of Serratia spp. (40% inducible and 60% derepressed mutants) and in 35.4% of the isolates of Citrobacter spp. (33% inducible and 66% derepressed mutants). Six isolates (four class B and two class A) of Serratia and eight isolates (seven class B and one class A) of Citrobacter spp. were MBL producers. Multiple mechanisms co-existed in eight isolates of Serratia and 15 isolates of Citrobacter spp. CPS was more effective in identifying ESBLs and inducible AmpC producers as well as type 1 carbapenemases than TZP and CAZ-CLAV were able to identify inducible AmpC producers. Conclusions: The high prevalence of ESBL, AmpC, and MBL in Serratia and Citrobacter species in this study suggests that detection of these by phenotypic methods in the absence of more specific molecular tests should be actively considered in not only developing countries but also in the developed world as this approach can lead to timely and appropriate antibiotic treatment. CPS may be advised due to the triple advantage of detection of all three types of beta-lactamases.